2001
DOI: 10.1177/0256090920010105
|View full text |Cite
|
Sign up to set email alerts
|

A Study of HRD Concepts, Structure of HRD Departments, and HRD Practices in India

Abstract: A number of human resources development frameworks has come into existence in the last ten years from various parts of the world. Indian organizations have begun to use these for improving their HRD systems and their impact. An Integrated HRD Systems Approach was evolved for Indian organizations at the Indian Institute of Management, Ahmedabad by Udai Pareek and T V Rao for L&T. This paper examines the current status of structuring of the HRD function and HRD subsystems in India against this “Integrated HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 3 publications
(5 reference statements)
0
16
0
Order By: Relevance
“…Using the Delphi Method to study 43 professionals from the top 1 to 3 HR associations in Korea (Lee, 2009); Bae et al (2004) studied training and development programs from 344 Korean companies Singapore A total of 5 000 managers participated in studies of HRD competency (Naquin et al, 2002) and professional HRD traits (Osman-Gani, 2002) Taiwan of China Used 266 valid questionnaires, studying 40.4 % small and medium-sized enterprises and 37.9 % large and medium-sized enterprises (Chen et al, 2005); also a study of HRD outputs of work (Lien, 2004) China's mainland Used research data from 7 provinces of China, 174 valid questionnaires, including 48.6 % state-owned enterprises, 27.7 % foreign enterprises, 14.5 % private enterprises, and 9.2% other organizations (Xie, 2005); 800 questionnaires to 12 companies in Shanghai, Nanjing, and Tianjin (Zhu, 1998); a training and development study of 310 technicians in Beijing (Hutchings, Kate, et al, 2009) India Uses a study from 252 enterprises, including 127 private enterprises, 99 public enterprises a , and 26 international enterprises (Yadapadithaya, 2001); Rao (2007) studied 12 representative companies Note: a. Public enterprises include state-owned and collective-owned enterprises.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the Delphi Method to study 43 professionals from the top 1 to 3 HR associations in Korea (Lee, 2009); Bae et al (2004) studied training and development programs from 344 Korean companies Singapore A total of 5 000 managers participated in studies of HRD competency (Naquin et al, 2002) and professional HRD traits (Osman-Gani, 2002) Taiwan of China Used 266 valid questionnaires, studying 40.4 % small and medium-sized enterprises and 37.9 % large and medium-sized enterprises (Chen et al, 2005); also a study of HRD outputs of work (Lien, 2004) China's mainland Used research data from 7 provinces of China, 174 valid questionnaires, including 48.6 % state-owned enterprises, 27.7 % foreign enterprises, 14.5 % private enterprises, and 9.2% other organizations (Xie, 2005); 800 questionnaires to 12 companies in Shanghai, Nanjing, and Tianjin (Zhu, 1998); a training and development study of 310 technicians in Beijing (Hutchings, Kate, et al, 2009) India Uses a study from 252 enterprises, including 127 private enterprises, 99 public enterprises a , and 26 international enterprises (Yadapadithaya, 2001); Rao (2007) studied 12 representative companies Note: a. Public enterprises include state-owned and collective-owned enterprises.…”
Section: Methodsmentioning
confidence: 99%
“…However, HRD in India has developed slowly. Rao et al (2007) investigated 12 companies in India, finding that more than half of those companies were without any full-time HRD employee and that the main task of full-time HRD employees is to implement the functions of recruitment and compensation, among others.…”
Section: The Comparison Of Hrd Rolesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Turnipseed (1990) nominated dimensions such as 'cohesion, autonomy, job involvement, innovation, general job orientation, work pressure, management control, supervisory support and job structure' (p. 247), all of which, according to Pace (2003), reside under the control of management practices, in particular, leadership practices. Rao's (1999) cultural elements of openness, confrontation, trust, authenticity, proactivity, autonomy, collaboration and experimenting -together with top management and HR staff styles -represent constituents in building organisational climate (Choudhury, 2011;Rao, Rao, & Yadav, 2007).…”
Section: Organisational Climate Measurementmentioning
confidence: 99%
“…Mehta and Kaur () observed that demographic features, the category of bank, the performance of the banks, and the dedication towards the public, influence the leadership styles. In another study, Rao and Rao () identified that the developmental leader style is the most appropriate style of leadership for any organization. According to the authors, this kind of leadership initiates growth and motivates the employees, and maximum content obtains.…”
Section: Introductionmentioning
confidence: 99%